Oral health and treatment needs across tribal and non-tribal groups: A tertiary care cross-sectional study - Sonal Saigal (Bioinformation, 2026)
Comparative oral health data for tribal and non-tribal populations in India remain limited, particularly regarding whether disparities reflect disease burden or healthcare access. This cross-sectional study assessed 343 participants (169 non-tribal, 174 tribal) at a tertiary care institution using WHO Basic Oral Health Survey (2013) criteria across three age strata. Overall caries experience differed statistically between the groups, although the absolute difference in mean affected surfaces was small (3.54 versus 3.52) Periodontal pocket (4–5 mm and ≥6 mm) and 4–5 mm attachment loss were significantly greater among tribal participants (p≤0.001 and p≤0.005). Prompt treatment, predominantly scaling, was required by a substantial proportion of participants in both groups (78.7% tribal versus 68.6% non-tribal). However, 55.7% of tribal participants had never accessed professional dental care, compared with 32.5% of non-tribal participants (p=0.027). Thus, data shows that disparities in dental service utilization may contribute substantially to oral health inequities between tribal and non-tribal populations, alongside differences in periodontal disease burden, underscoring the need for access-focused, community-based interventions.